2011
DOI: 10.1063/1.3549835
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic evidence of the formation of (V,Ti)O2 solid solution in VO2 thinner films grown on TiO2(001) substrates

Abstract: We have prepared VO 2 thin films epitaxially grown on TiO 2 (001) substrates with thickness systematically varied from 2.5 to 13 nm using a pulsed laser deposition method, and studied the transport property and electronic states of the films by means of resistivity and in situ synchrotron photoemission spectroscopy (SRPES). In resistivity measurements, the 13-nm-thick film exhibits a metal-insulator transition at around 290 K on cooling with change of three orders of magnitudes in resistivity. As the film thic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 27 publications
2
29
0
Order By: Relevance
“…A similar increase in resistivity and suppression of the MIT have been reported for VO 2 films grown on single-crystal TiO 2 substrates at high growth temperatures, and they have been attributed to interdiffusion of Ti and V atoms at the interface. 20,21 In fact, we confirmed by means of secondary-ion mass spectroscopy that Ti atoms diffused into a VO 2 film grown at 770 K (data not shown).…”
Section: Resultssupporting
confidence: 84%
“…A similar increase in resistivity and suppression of the MIT have been reported for VO 2 films grown on single-crystal TiO 2 substrates at high growth temperatures, and they have been attributed to interdiffusion of Ti and V atoms at the interface. 20,21 In fact, we confirmed by means of secondary-ion mass spectroscopy that Ti atoms diffused into a VO 2 film grown at 770 K (data not shown).…”
Section: Resultssupporting
confidence: 84%
“…It is reported that nanoscale line cracks due to thermal stress can induce strain relaxation in VO 2 films with thicknesses ranging from 10 to 30 nm [16]. In addition, if the thickness is only within several nanometers, the VO 2 films will show exotic properties [21,22]. Moreover, the thickness also affects the performance in VO 2 -based nanoscale devices [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…The limited interdiffusion and consistent tetravalent oxidation state of vanadium throughout the film make it possible for substantially thinner VO 2 films to exhibit MITs. 4,27,28 The growth process described has yielded the thinnest films yet to show an MIT and the only VO 2 thin films grown by MBE to show an MIT.…”
Section: -13mentioning
confidence: 99%